2011
DOI: 10.1111/j.1749-6632.2011.06195.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrodysplasia ossificans progressiva: a blueprint for metamorphosis

Abstract: The most important milestone in understanding a genetic disease is the identification of the causative mutation. However, such knowledge is often insufficient to decipher the pathophysiology of the disorder or to effectively treat those affected. Fibrodysplasia ossificans progressiva (FOP) is a rare, disabling, genetic disease of progressive heterotopic endochondral ossification (HEO) enabled by missense mutations that promiscuously and provisionally activate ACVR1/ALK2, a bone morphogenetic protein (BMP) type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 39 publications
1
24
0
1
Order By: Relevance
“…For example, the application of compressive forces in tendon can induce fibrocartilaginous phenotypes, which is lost when the mechanical stimulation is removed3637. Inflammation can also trigger heterotopic endochondral ossification, as established by several studies of traumatic or neurogenic injuries and congenital diseases383940. In addition, a recent study showed that the tendon transcription factor Mkx may also function to inhibit chondrogenic differentiation in tenocytes;41 our study showed downregulation of Mkx expression after adult tendon injury, which may permit cartilage differentiation at the expense of tenogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the application of compressive forces in tendon can induce fibrocartilaginous phenotypes, which is lost when the mechanical stimulation is removed3637. Inflammation can also trigger heterotopic endochondral ossification, as established by several studies of traumatic or neurogenic injuries and congenital diseases383940. In addition, a recent study showed that the tendon transcription factor Mkx may also function to inhibit chondrogenic differentiation in tenocytes;41 our study showed downregulation of Mkx expression after adult tendon injury, which may permit cartilage differentiation at the expense of tenogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Given the apparently equivalent consequence of K27M mutations in H3.1 or H3.3 to decrease total cellular levels of H3K27me3, the significant co-occurrence of ACVR1 and HIST1H3B mutations may reflect a specific developmental setting. Surprisingly, some of the same somatic ACVR1 mutations identified in DIPG are found as heterozygous germline mutations causing the congenital malformation syndrome fibrodysplasia ossificans progressiva (FOP), a disease characterized by the formation of heterotopic ossifications in soft tissues at sites of inflammation 82, 83 . FOP is not associated with cancer predisposition, despite the presence of germline mutations that are identical to those found in DIPG.…”
Section: Acvr1/alk2 Mutations; a Selective Role For Bmp Signaling In mentioning
confidence: 99%
“…The most common mutation is a heterozygous single nucleotide substitution c.617G>A in ACVR1 (located on chromosome 2q23-24) which encodes activin receptor type 1 (ACVR1) also known as activin like kinase 2 (ALK2), a bone morphogenetic protein (BMP) type I receptor. This mutation leads to a R206H substitution in the glycine-serine region of the cytoplasmic domain of ACVR1, which is highly conserved [1,3,4]. This gain-of-function mutation leads to dysregulated enhanced BMP signaling, responsible for the new bone formation in connective tissue, as occurring in this condition.…”
Section: Discussionmentioning
confidence: 99%